Effectiveness of Anti-SARS-CoV-2 monoclonal antibodies in real-life: RNAemia and clinical outcomes in high-risk COVID-19 patients - Matteo Domenico Marsiglia; Silvia Bianchi; Francesca Bai; Camilla Tincati; Emerenziana Ottaviano; Silvia Ancona; Giulia Marchetti; Elisa Borghi (PLoS ONE, 2025)
Background Anti-SARS-CoV-2 neutralizing monoclonal antibodies (mAbs) have been shown to have clinical benefits in treating high-risk patients with mild-moderate COVID-19. SARS-CoV-2 RNA in serum (RNAemia), is usually associated with severe disease and deaths. This study evaluates real-life data on the effectiveness of mAbs therapies against SARS-CoV-2 infections by different viral variants, particularly in the presence of RNAemia, focusing on clinical outcomes. Methods From March 2021 to May 2022, high-risk patients with PCR-confirmed mild-moderate COVID-19 were enrolled at the Clinic of Infectious Diseases, San Paolo Hospital in Milan. Patients received Bamlanivimab/Bamlanivimab + Etesevimab/Casirivimab + Imdevimab/Sotrovimab based on Agenzia Italiana del Farmaco (AIFA) guidelines and prevalent SARS-CoV-2 variants. Nasopharyngeal swabs (NPS) and plasma samples were collected at infusion (t0) and after 7 days (t1). NPS viral loads and RNAemia were quantified using RT-qPCR, and variant typing was conducted. Clinical outcomes were evaluated, including time to symptom resolution and adverse effects. Results Among 176 enrolled patients, treatment efficacy was observed in 96.6% with a median time to symptom resolution of 12 days (IQR 10–19). Viral load significantly decreased in both NPS and plasma by day 7 post-treatment (p<0.001). At t0, RNAemia was present in 61.9% of patients and NPS viral loads were higher in patients with RNAemia (p=0.002). However, after treatment, no significant differences in viral loads and times to symptom resolution were noted between patients with and without RNAemia. Omicron-infected patients exhibited higher plasma viral loads compared to Alpha and Delta variants (p<0.001) and the presence of RNAemia was significantly associated with Omicron (p<0.001). Vaccinated patients achieved faster recovery regardless of variant type (p=0.001). Conclusion Early administration of anti-SARS-CoV-2 mAbs in high-risk patients significantly reduced viral loads in NPS and plasma and improved clinical outcomes. Despite the presence of RNAemia, these tailored mAb therapies led to favorable recovery times and minimal adverse effects.